Odor-Induced Vomiting Is Combinatorially Triggered by Palp Olfactory Receptor Neurons That Project to the Lobus Glomerulatus in Locust Brain - Sun, Liyuan; Pan, Xueqin; Li, Hongwei; Zhang, Xinyang; Zhao, Xincheng; Zhang, Liwei; Zhang, Long (Frontiers in Physiology, 2022)
Although vomiting is commonly recognized as a protective reaction in response to toxic stimuli, the elaborate sensory processes and necessary molecular components are not fully clear, which is due to a lack of appropriate experimental animal models. Vomiting reflex to volatile chemicals renders locust one candidate for vomiting model. Here, we identified a panel of chemical cues that evoked evident vomiting in locust nymphs and demonstrated the selected combinatorial coding strategy that palps but not antennae olfactory receptor neurons (ORNs) employed. Specifically, knocking down individual palp odorant receptors (ORs) such as OR17, OR21, and OR22 attenuated the vomiting intensity evoked by E-2-hexenal and hexanal, while suppression of OR12 and OR22 augmented vomiting to E-2-hexenal and 2-hexanone, respectively. Furthermore, dual-RNAi treatment against OR17 or OR21 together with OR22 resulted in a much lower response intensity than that of individual OR suppression. Furthermore, OR12 was revealed in palp sensilla basiconica (pb) subtype 3 to tune the neuronal decaying activity to E-2-hexenal. Finally, anterograde labeling indicated that palp ORNs primarily projected into the lobus glomerulatus (LG), and the projection neurons (PNs) in the LG further projected into the accessary calyx (ACA). Together, the establishment of an olfaction-inducible vomiting model in locusts deepens the understanding of olfactory coding logics and provides an opportunity to clarify the neural basis underlying animal vomiting.